Realist agency and phenomenological subjectivity: friends or foes? - Yip, Ka Lok (Journal of Critical Realism, 2025)
In defending 'analytical dualism', Margaret Archer drew on a more objectivist reading of phenomenology to support her critical realist conception of human agency. In developing the philosophy of metaReality and its central tenet of 'non-duality', Roy Bhaskar articulated a unified vision of human agency and the world that resonates with a more subjectivist reading of phenomenology. This article seeks to extend and deepen our understanding of human agency by 'underlabouring' the relationship among critical realist analytical dualism, metaRealist non-duality and phenomenology in their respective conceptualizations of agency. It argues that unlike the rivalry between the objectivist and subjectivist readings of phenomenology, the shared commitment to a stratified ontology renders the different accounts of agency in critical realist analytical dualism and metaRealist non-duality compatible and complementary. It then revisits a recurrent theme in existential phenomenology, individuals' freedom in war, to illustrate the divergence, convergence and relationship among all three approaches.